Characterisation of the effects of the chemotherapeutic agent paclitaxel on neuropathic pain-related behaviour, anxiodepressive behaviour, cognition, and the endocannabinoid system in male and female rats - Di Marino, Chiara; Llorente-Berzal, Álvaro; Diego, Alba M.; Bella, Ariadni; Boullon, Laura; Berrocoso, Esther; Roche, Michelle; Finn, David P. (Frontiers in Pharmacology, 2025)
Paclitaxel (PTX) is a commonly used chemotherapeutic drug, however, one of its major adverse effects is chronic neuropathic pain, with the incidence being higher in women than in men. The neurobiological mechanisms behind this sex difference are still largely unclear, and the endocannabinoid system, which exhibits sexual dimorphism and plays a key role in pain regulation, is a promising area for further studies. The present study aimed to characterise pain-, cognition-, anxiety-, and depression-related behaviours in male and female rats following PTX administration, and associated alterations in the endocannabinoid system. After the induction of the model, pain-related behaviours were assessed using von Frey, Acetone Drop and Hargreaves’ tests, Novel Object Recognition and T-Maze Spontaneous Alternation tests were used for cognition-related behaviours, Elevated Plus Maze, Open Field, and Light Dark Box tests were used to assess anxiety-related behaviours, and Sucrose Preference, Sucrose Splash, and Forced Swim tests for depression-related behaviours. At each time point analysed, animals treated with PTX exhibited mechanical and cold hypersensitivity, with females displaying lower hind paw withdrawal thresholds to mechanical stimulation than males. No PTX-induced alterations in the other behavioural tests were detected. Post-mortem measurement of endocannabinoid and related N-acylethanolamine levels in spinal cord and discrete brain regions revealed a PTX-induced increase of 2-Arachidonoyl Glycerol (2-AG), N-Palmitoylethanolamine (PEA) and N-Oleoylethanolamine (OEA) levels in the amygdala of male and female animals, but not in the other areas. Collectively, these results suggest that PTX causes similar long-lasting hypersensitivity to mechanical and cold stimuli, but not heat, in rats of both sexes, effects accompanied by increases in amygdalar levels of endocannabinoids and N-acylethanolamines.